COINS IN ARCHAEOLOGICAL CONTEXT (II). THE CIVILIAN BATHS OF THE AUXILIARY FORT FROM SUTOR (ROMANIA, SĂLAJ COUNTY) - Cristian Gazdac; Vlad Andrei Lazarescu; Sorin Ilie Cocis; Sergiu Traian Socaciu (Journal of Ancient History and Archaeology)
The present paper is presenting a case study of a rescue archaeological investigation following the building of a motorway. The research area revealed the civilian baths complex of the Roman auxiliary fort of Optatiana in the province of Dacia (today, Sutor, Sălaj County, Romania). The analysis of coin finds, issuers, types, denominations, within the archaeological contexts they were found in, reveal the fact that only one-two coins may lead the archaeologist into a chronological pitfall, while a group of more than five single finds with similar dating elements (e.g. same issuer or his successor(s) from the same context/phase may be a true help in understanding the development of an archaeological complex.